Biomarkers responses of the clam Anomalocardia flexuosa in sediment toxicity bioassays using dredged materials from a semi-arid coastal system - Moreira, Lucas Buruaem [UNESP]; Sasaki, Silvio Tarou; Taniguchi, Satie; Peres, Tiago Farias; Lopes Figueira, Rubens Cesar; Bícego, Marcia Caruso; Marins, Rozane Valente; Costa-Lotufo, Leticia Veras; Souza Abessa, Denis Moledo [UNESP] (Elsevier, 2020)
Few test organisms are employed for sediment toxicity assessments in Tropical regions, including Brazil. We assessed the ability of the clam Anomalocardia flexuosa to respond to contamination in sediment bioassays using dredging materials of a semi-arid region (Ceará State, NE Brazil), with attention to sublethal responses. Sediments were collected during and after dredging (survey 1 and 2, respectively) and animals exposed in laboratory over 28 days, with responses measured at 7 days. Bioaccumulation of contaminants was determined in whole-body soft tissues as a metric of bioavailability, and biomarkers' changes were monitored in terms of enzymes of phase I and II metabolism, acetylcholinesterase (AChE), and antioxidant responses, lipid peroxidation (LPO) and DNA damage (strand breaks). Clams accumulated aliphatic (AHs) and aromatic hydrocarbons (PAHs), and linear alkylbenzenes (LABs) compared to control conditions (day 0), with increased amounts of As, Cd, Cu, and Zn observed in some samples. The enzyme glutathione S-transferase was enhanced in animals exposed to samples, indicating activation of phase II metabolism. Changes observed in glutathione peroxidase (GPx), glutathione reductase (GR), LPO and strand breaks were related to oxidative stress. AChE enzymatic activity also changed, as an indicator of neurotoxicity caused by sediment exposure. The computed integrated biomarker response index (IBR) ranked sites according to the contamination status and proximity to its sources. Correlations found for biomarkers and bioaccumulation of hydrocarbons indicated the influence of harbor activities, effluent discharges, and urban runoff on the sediment pollution of Mucuripe Bay. Data also showed that SQGs are unable to predict bioaccumulation and subchronic effects. Based on our results we consider that biomarkers responses in A. flexuosa are important endpoints to be applied in sediment toxicity bioassays in tropical regions.

Bioaccumulation; Environmental monitoring; Linear alkylbenzenes; Marine pollution; Metals; Polycyclic aromatic hydrocarbons; Sublethal effects; Tropical environments; Toxicity testing; Weight of evidence; Ecological health; Marine biology; Environmental assessment; Environmental hazard; Environmental health; Environmental impact assessment; Environmental pollution; Environmental risk assessment; Environmental toxicology; Toxicology
Keywords: Bioaccumulation; Ecological health; Environmental assessment; Environmental hazard; Environmental health; Environmental impact assessment; Environmental monitoring; Environmental pollution; Environmental risk assessment; Environmental toxicology; Linear alkylbenzenes; Marine biology; Marine pollution; Metals; Polycyclic aromatic hydrocarbons; Sublethal effects; Toxicity testing; Toxicology; Tropical environments; Weight of evidence